PENGARUH MOTIVASI KERJA DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI BALAI BESAR PENELITIAN VETERINER KOTA BOGOR (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The thesis entitled “The Influence of Work Motivation and Teamwork on Employee Performance of the Bogor City Veterinary Research Center was written by Hafid Rachmat Febriansyah, NPM 181104010600, Under the guidance of: Dr.M.Aziz Firdaus, S.E.,M.M and Hj. Rachamatullaily, S.E., M.M Bogor City Veterinary Research Center (BB Litvet) is a technical implementation unit within the scope of a research agency under the coordination of the Center for Research and Development of Animal Husbandry (Puslitbangnak). The Bogor City Veterinary Research Center is established based on the regulation of the Minister of Agriculture number 34/permentan/OT.140/2013 concerning the organization and working procedures of the Veterinary Research Center with echelon II/b level and has the main task of carrying out veterinary research tasks. The choice of work motivation and teamwork at the Center for Veterinary Research as research subjects to determine the existence of work motivation and teamwork within the company, because work motivation has an effect as the most vital driving force in achieving performance. This study aims to determine the effect of work motivation on employee performance at the Bogor City Veterinary Research Center, to determine the effect of Teamwork on Employee Performance at the Bogor City Veterinary Research Center. The tests used in this study include Validity Test, Reality Test, Linearity Test, Homogeneity Test, Normality Test and t Test and f Test. Based on a discussion of the results of a study titled ``Effect of work motivation and teamwork on employee performance'' at the Bogor City Veterinary Research Center, we found that work motivation (X1) and teamwork (X2) It was concluded that it affects performance.